Editorial - Sulaiman, Kabuye Uthman; U Tun Aung, Maulana Akbar Shah (IIUM Press, 2023)
The call for this special issue was prompted by the International Conference on Women Empowerment deliberations. The conference, held on 10th December 2022 at International Islamic University Malaysia (IIUM), was inaugurated by Dr. Maulana Akbar Shah @ U Tun Aung, Head of Research in the department of Fundamental and Inter-Disciplinary Studies, AbdulHamid AbuSulayman Kulliyyah of Islamic Revealed Knowledge and Human Sciences (AHAS KIRKHS), who delivered a welcoming speech, followed by opening remarks by Prof. Shukran Bin Abd Rahman, Dean of AHAS KIRKHS. The event also featured speeches by distinguished guests, including the Honourable Rector of IIUM, Professor Emeritus Tan Sri Dato’ Dzulkifli bin Abdul Razak and Mr. Thomas Albrecht, Representative of UNHCR, Malaysia, Prof. Abdul Aziz Berghout, the Dean of the International Institute of Islamic Thought and Civilisation (ISTAC), IIUM, and Prof. Dawood Al-Hidabi, Director of International Institute for Muslim Unity (IIMU), IIUM.